Decision making support under conditions of incomplete consistency of expert advantages - Beskorovainyi, Volodymyr; Kolesnyk, L.; Russkin, Volodymyr (My University, 2022)
Для розширення перспектив інтелектуалізації процедур проєктування й управління складними об’єктами запропоновано рішення актуальної науково-прикладної задачі підвищення ефективності технологій підтримки прийняття багатокритеріальних рішень. Запропоновано комбінований метод оцінювання варіантів в умовах неповної узгодженості переваг експертів. Для оцінювання важливості часткових критеріїв запропоновано використовувати методи зменшення дисперсії та штрафування неузгодженості, які дозволяють підвищувати точність оцінок вагових коефіцієнтів часткових критеріїв. За умови невисокої точності визначення вагових коефіцієнтів для оцінки ефективності рішень запропоновано використовувати універсальну функцію загальної корисності, яка шляхом зміни одного з параметрів дозволяє реалізувати стратегії пошуку як максимально ефективних, так і максимально стійких рішень. Практичне використання запропонованого методу дозволить за рахунок підвищення точності оцінювання вагових коефіцієнтів часткових критеріїв отримувати більш ефективні рішення задач багатокритеріальної оптимізації. Напрямком подальших досліджень може бути розробка ефективних методів підтримки прийняття рішень для нечітко або інтервально заданих характеристик варіантів. To expand the prospects of intellectualization of design and management procedures for complex objects, a decision of an urgent scientific and applied problem of increasing the efficiency of multicriteria decision support technologies is proposed. A combined method for evaluating variants under conditions of incomplete consistency of expert advantages is proposed. To assess the importance of partial criteria it was proposed to use methods of reducing variance and penalizing inconsistency, allowing to increase the accuracy of assessments of weight coefficients of partial criteria. With low accuracy in determining the weighting coefficients to assess the effectiveness of decisions it is proposed to use a universal common utility function, which by changing one of the parameters allows to implement strategies for finding both the most effective and the most sustainable decisions. Practical use of the proposed method will allow to obtain more effective decisions to multi-criteria optimization problems by increasing the accuracy of assessment of weight coefficients of partial criteria. The direction of further research may be the development of effective decision support methods for fuzzy or interval characteristics of variants.
Beskorovainyi V. Decision making support under conditions of incomplete consistency of expert advantages / V. Beskorovainyi, L. Kolesnyk, V. Russkin // Innovative integrated computer systems in strategic project management : Collective monograph edited by I. Linde. European University Press. – Riga : ISMA, 2022. – Р. 16–26.
Keywords: багатокритеріальна оптимізація, зменшення дисперсії, неповна узгодженість переваг експертів, підтримка прийняття рішень, універсальна функція загальної корисності, ефективні рішення, стійкі рішення; multi-criteria optimization, variance reduction, incomplete consistency of experts' preferences, decision support, universal utility function, efficient solutions, sustainable solutions